Taking affective explanations to heart - Deonna, Julien A.; Teroni, Fabrice (Social Science Information, 2009)
In this article, the authors examine and debate the categories of emotions, moods, temperaments, character traits and sentiments. They define them and offer an account of the relations that exist among the phenomena they cover. They argue that, whereas ascribing character traits and sentiments (dispositions) is to ascribe a specific coherence and stability to the emotions (episodes) the subject is likely to feel, ascribing temperaments (dispositions) is to ascribe a certain stability to the subject’s moods (episodes). The rationale for this distinction, the authors claim, lies in the fact that, whereas appeal to character traits or sentiments in explanation is tantamount to making sense of a given behaviour in terms of an individual’s specific evaluative perspective — as embodied in this individual’s emotional profile — appeal to temperaments makes sense of it independently of any such evaluative perspective. Dans cet article, les auteurs s’interrogent sur les catégories d’émotions, d’humeurs, de tempéraments, de traits de caractère et de sentiments. Ils proposent des définitions de ces catégories et offrent une analyse des relations existant entre les phénomènes qu’elles désignent. Ils défendent ainsi l’idée selon laquelle attribuer des traits de caractère et des sentiments (dispositions) revient à attribuer une certaine stabilité et cohérence dans les émotions (épisodes) ressenties par le sujet, alors qu’attribuer des tempéraments (dispositions) revient à attribuer une certaine stabilité dans ses humeurs (épisodes). Cette distinction est motivée par les rôles explicatifs distincts joués par ces catégories. D’un côté, faire référence à des traits de caractère ou à des sentiments dans l’explication psychologique, c’est faire sens d’un comportement donné en termes de l’orientation évaluative d’un individu, en tant qu’elle s’incarne dans son profil émotionnel. De l’autre, lorsque l’on fait appel à des tempéraments, l’explication est indépendante d’une quelconque perspective évaluative.